Analisis Pengendalian Persediaan Bahan Baku Jagung untuk Proses Produksi Pakan Ternak di PT.Japfa Comfeed Indonesia Tbk. Unit Gedangan Sidoarjo dengan Metode EOQ - ILHAM, SAPUTRA; Stighfarrinata, Rizky (Jurnal Teknologi dan Manajemen Sistem Industri, 2023)
PT. Japfa Comfeed Indonesia, Tbk is an animal feed company that uses corn as its primary raw material. The company enforces strict management to ensure high-quality feed production. Procurement focuses on corn quality before purchase, followed by comprehensive quality control. This study uses the Economic Order Quantity (EOQ) method to analyze inventory management at PT. Japfa Comfeed Indonesia, Tbk. The research examines current practices, models a raw material management system, and suggests improvements in planning and control. The aim is to optimize production processes and reduce inventory costs using EOQ. The results show that applying EOQ leads to a larger order quantity (6,957,354 kg) compared to the current order quantity (1,705,051 kg), with fewer annual orders (3 versus 12). Additionally, using EOQ reduces ordering costs from Rp. 318,000,000 to Rp. 79,500,000, demonstrating improved inventory efficiency and enhanced production planning.